2012
DOI: 10.1371/journal.pone.0046063
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of poly(ADP-ribose) Polymerase Interferes with Trypanosoma cruzi Infection and Proliferation of the Parasite

Abstract: Poly(ADP-ribosylation) is a post-translational covalent modification of proteins catalyzed by a family of enzymes termed poly(ADP-ribose) polymerases (PARPs). In the human genome, 17 different genes have been identified that encode members of the PARP superfamily. Poly (ADP-ribose) metabolism plays a role in a wide range of biological processes. In Trypanosoma cruzi, PARP enzyme appears to play a role in DNA repair mechanisms and may also be involved in controlling the different phases of cell growth. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 39 publications
0
35
3
Order By: Relevance
“…Additionally, inos expression is significantly reduced in the presence of noncleavable PARP1 (D214N), compared to cleavable PARP1 (WT or enzymatically inactive) [64]. It was recently demonstrated that treatment with Olaparib (a pharmacological inhibitor of PARP-1 enzymatic activity) reduced T. cruzi replication in VERO cells [65]. However, the enzymatic activity of PARP-1 is not related to the role of cleaved PARP-1 in the regulation of chromatin condensation and access to transcription factors [60].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, inos expression is significantly reduced in the presence of noncleavable PARP1 (D214N), compared to cleavable PARP1 (WT or enzymatically inactive) [64]. It was recently demonstrated that treatment with Olaparib (a pharmacological inhibitor of PARP-1 enzymatic activity) reduced T. cruzi replication in VERO cells [65]. However, the enzymatic activity of PARP-1 is not related to the role of cleaved PARP-1 in the regulation of chromatin condensation and access to transcription factors [60].…”
Section: Discussionmentioning
confidence: 99%
“…The T. cruzi PARP (TcPARP) poly(ADP-ribose) synthesis is activated by DNA strand breaks in vitro but also in vivo, as observed by the accumulation of PAR in the nuclei of T. cruzi epimastigotes. The activity is also inhibited by 3-aminobenzamide (61) but also by next-generation inhibitors such as olaparib (64). PARP activity is normally counterbalanced by a glycohydrolase activity, which hydrolyzes the polymers present on PARP, thereby allowing a new cycle of automodification.…”
Section: Poly(adp-ribose) Polymerasementioning
confidence: 99%
“…Another way of taking advantage of the major role of PARP is to inhibit the protein in order to impair DNA repair mechanisms and therefore cell proliferation and drug resistance. Some PARP inhibitors were tested in T. cruzi, where PARP inhibition was effective on the amastigote but not the trypomastigote forms in cell culture (64). Pretreatment of parasites with the PARP inhibitor Olaparib decreased the number of intracellular amastigotes in infected cells.…”
Section: Resistance and Treatmentmentioning
confidence: 99%
“…The T. cruzi strain most frequently employed was Tulahuen (TcVI; n  = 7), followed by the Y strain (TcII; n  = 4) and EP isolate (not classified into DTU; n  = 4). MOI, taken directly or calculated from all studies, ranged from 1 [35] to 50 parasites per host cell [34]. Parasite-cell incubation times were widely spread, from 2 h [19] to as long as 6 days [22].…”
Section: Resultsmentioning
confidence: 99%
“…When the MOI and FCS concentration were increased, infectivity was enhanced. In contrast, after 96 h of incubation, CL Brener-infected cells displayed 20.8% infection and less than three amastigotes per cell despite using a MOI which is 10 times higher than in experiments with EP [34]. Furthermore, infectivity in Vero cells with the EP isolate was higher than that seen with BEC isolate when using identical conditions [21].…”
Section: Resultsmentioning
confidence: 99%